2022
DOI: 10.3389/fspas.2022.1032099
|View full text |Cite
|
Sign up to set email alerts
|

Flare quasi-periodic pulsation associated with recurrent jets

Abstract: Quasi-periodic pulsations (QPPs), which carry time features and plasma characteristics of flare emissions, are frequently observed in light curves of solar/stellar flares. In this study, we investigated non-stationary QPPs associated with recurrent jets during an M1.2 flare on 2022 July 14. A quasi-period of ∼45±10 s, determined by the wavelet transform technique, is simultaneously identified at wavelengths of soft/hard X-ray and microwave emissions, which are recorded by the Gravitational Wave High-Energy Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…The third type may be caused by changes in the magnetic field configuration during the first reconnection, which affects the subsequent eruption. Most of these jets also show repeated blobs, which could arise from the quasi-periodic reconnection that has been observed in some solar flares (Shi et al 2022a,b;Li et al 2022). By combining the Solar Orbiter/EUI observation with a simultaneous observation from SDO/AIA, the jets' physical parameters and energies were measured.…”
Section: Discussionmentioning
confidence: 99%
“…The third type may be caused by changes in the magnetic field configuration during the first reconnection, which affects the subsequent eruption. Most of these jets also show repeated blobs, which could arise from the quasi-periodic reconnection that has been observed in some solar flares (Shi et al 2022a,b;Li et al 2022). By combining the Solar Orbiter/EUI observation with a simultaneous observation from SDO/AIA, the jets' physical parameters and energies were measured.…”
Section: Discussionmentioning
confidence: 99%
“…Mishra et al [46] found a period of about 3 min in a blowout jet mainly composed of cool material and the research strongly supports the fact that multiple magnetic reconnection triggers QPPs in the blowout jet. Li et al [47] suggest that the flare QPPs could be excited by recurrent jets, and they should be associated with non-thermal electrons that are periodically accelerated by a repeated energy release process, such as repetitive magnetic reconnection.…”
Section: Discussionmentioning
confidence: 99%
“…QPPs have been identified with timescales ranging from seconds to minutes (e.g. Zhao et al 2023;Kou et al 2022;Lörinčík et al 2022;Li et al 2022;Zimovets et al 2022), with few studies reporting subsecond QPPs (e.g. Knuth & Glesener 2020;Qiu et al 2012).…”
Section: Introductionmentioning
confidence: 99%